Experiential Avoidance, Self-compassion, Self-judgment and Coping Styles in Infertility - Cunha, Marina (2018)
Objectives: This study sought out to explore the existence of differences regarding emotion regulation processes (psychological inﬂexibility/experiential avoidance,self-judgment and self-compassion) and coping styles (emotional/detached, avoidant and rational) in three different groups of couples: 120 fertile couples(FG), 147 couples with an infertility diagnosis who were pursuing medical treatment for their fertility problem(s) (IG), and 59 couples with infertility applying for adoption (AG). Study design: Cross-sectional survey, using the couple as unit of analysis. Main outcome measures: Participants ﬁlled in paper-pencil questionnaires assessing coping styles, psychological inﬂexibility/experiential avoidance, self-judgment and self-compassion. Results: IG couples, and particularly women, tend to use more experiential avoidance and self-judgment mechanisms and less emotional/detached coping style. When compared to FG couples, IG and AG couples tend to apply more avoidant coping strategies. AG couples showed higher self-compassion. Conclusions: Findings suggest that emotion regulation processes may be an important target in psycho-logical interventions for patients dealing with infertility and with the demands of medical treatment.